Substantial and Private Autonomy Equality in Civil Code 2002 - Borges, Roxana Cardoso Brasileiro (2016)
Under the influence of doctrinal current that advocates the constitutionalizsation of civil law, expanded the discussion on the promotional role of the Civil Code of 2002 with regard to substantive equality. In this paper, we try to analyze the instruments offered by the novel encoding for the realization of the aforementioned equality, as opposed to the protection of formal equality erected by the nineteenth-century encodings, and in Brazil, the Civil Code of 1916. Located historically in a statement period prestacionais rights and built based on different coding guidelines of the Brazilian 1916, the new Civil Diploma features, even if timid and insufficient, suitable instruments to the achievement of the aforementioned substantive equality, which are forgotten by significant doctrinal contingent because of valuation in excess of the phenomenon called constitutionalization of law.